2001
DOI: 10.1046/j.1365-2222.2001.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

NAC Manchester Asthma and Allergy Study (NACMAAS): risk factors for asthma and allergic disorders in adults

Abstract: Asthma and atopic disorders are the most common chronic diseases in the developed countries. Knowledge of the risk factors for these disorders may facilitate the development of preventive strategies aimed at reducing prevalence rates. To investigate the risk factors for asthma and allergic diseases in a large number of adults who are the parents of children in the National Asthma Campaign Manchester Asthma and Allergy Study. All pregnant women and their partners attending "Booking" antenatal clinics were invit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
83
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 34 publications
9
83
2
2
Order By: Relevance
“…In our study, the prevalence of allergic sensitization among subjects from 17 to 69 years was 33.0%, while the prevalence among adults aged 20–44 years was 38.5%. The prevalence seems similar to findings in Western European countries ranging from 21 to 50% [17,18,19,20,21,22]. …”
Section: Discussionsupporting
confidence: 86%
“…In our study, the prevalence of allergic sensitization among subjects from 17 to 69 years was 33.0%, while the prevalence among adults aged 20–44 years was 38.5%. The prevalence seems similar to findings in Western European countries ranging from 21 to 50% [17,18,19,20,21,22]. …”
Section: Discussionsupporting
confidence: 86%
“…In the Manchester Asthma and Allergy Study, sensitizations to dust mites, cats, dogs, and mixed grasses were all independently associated with asthma. The ORs for current asthma increased with the increasing number of positive skin tests [39]. In another study of children 7 or 8 years of age, sensitization to common indoor allergens, including cat, dust mite, and cockroach, was independently associated with bronchial hyperresponsiveness, with ORs ranging from 4 for cockroach to 15 for cat sensitization [40].…”
Section: Sensitization To Indoor Allergens and Allergymentioning
confidence: 93%
“…In a pooled analysis of more than 58,000 children, an association was found between visible mold exposure and respiratory and allergic symptoms [45]. In another study, dog ownership was significantly and directly associated with asthma development [39].…”
Section: Exposure To Indoor Allergens and Allergymentioning
confidence: 95%
See 1 more Smart Citation
“…Numerous epidemiological studies have demonstrated that atopic sensitization is a strong risk factor for asthma in childhood (1, 2) and adulthood (3), both in the developed (3) and in the developing countries (1,2,4), supporting the notion that asthma is in part an allergic disease. However, the role of allergy in severe asthma remains the issue of considerable controversy.…”
mentioning
confidence: 92%